2004
DOI: 10.1007/s00535-004-1398-6
|View full text |Cite
|
Sign up to set email alerts
|

Results of triple eradication therapy in Japanese children: a retrospective multicenter study

Abstract: The PAC regimen is effective in children. Clarithromycin resistance is associated with eradication failure. Metronidazole is a good substitute for clarithromycin as the second-line option for children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
4
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 24 publications
5
49
4
1
Order By: Relevance
“…Indeed, eradication rates in children treated with a first-line regimen of PPI, AMPC and CAM are also decreasing related to increased antibiotic resistance especially to CAM. In the past, multicenter studies in Japan reported H. pylori eradication rates in children achieving with PPI, AMPC and CAM were 70.6% to 77.4% [39] [41]. Consistent with previous studies in adults, the eradication rate has decreased in pediatric patients infected with CAM resistant strains to 40.0% -57.1% [37] [39].…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Indeed, eradication rates in children treated with a first-line regimen of PPI, AMPC and CAM are also decreasing related to increased antibiotic resistance especially to CAM. In the past, multicenter studies in Japan reported H. pylori eradication rates in children achieving with PPI, AMPC and CAM were 70.6% to 77.4% [39] [41]. Consistent with previous studies in adults, the eradication rate has decreased in pediatric patients infected with CAM resistant strains to 40.0% -57.1% [37] [39].…”
Section: Discussionsupporting
confidence: 63%
“…In the past, multicenter studies in Japan reported H. pylori eradication rates in children achieving with PPI, AMPC and CAM were 70.6% to 77.4% [39] [41]. Consistent with previous studies in adults, the eradication rate has decreased in pediatric patients infected with CAM resistant strains to 40.0% -57.1% [37] [39]. Since the goal of treatment is at least a 90% eradication rate on a per-protocol basis at the first attempt [45], recent eradication rate of the firstline therapy with PPI, AMPC and CAM strongly suggests the need for new approaches.…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly tested regimen contained a combination of PPI, clarithromycin, and amoxicillin, followed by triple therapies containing PPI, clarithromycin, and nitroimidazoles, or bismuth, clarithromycin, and nitroimidazoles (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). The reasons for the great variability of the eradication rates observed in the studies include small sizes of study populations, differences between study populations, and variation in the total daily dose, dosing frequency and duration of treatment components, as well as in time of posttreatment follow-up and methods used to assess eradication after treatment.…”
Section: Resultsmentioning
confidence: 99%
“…At present, in the pediatric population, five randomized studies have evaluated whether consumption of probiotics could increase H. pylori eradication rates and reduce the side effects of treatment (36)(37)(38)(39)(40).These trials do not provide evidence on the beneficial effect in children of supplementation of probiotics to triple therapy for eradicating H. pylori infection nor for positively (16,19,(43)(44)(45)(46) S: sensitive; R: Resistant affecting therapy-related symptoms and overall treatment tolerance. However, the five studies are all based on relatively small samples and lack the statistical power necessary to detect an important effect of the probiotics.…”
Section: Finland! Multicentermentioning
confidence: 99%
“…At this moment, in Europe only omeprazole and esomeprazole are approved [18]. Almost all published efficacy studies in pediatric patients have been performed with omeprazole and lansoprazole [19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37] used in combination therapies for the first-line treatment of H. pylori eradication. The North American Society for Pediatric Gastroenterology, Hepatology and Nutrition published clinical practice guidelines on the use of omeprazole for management of gastroesophageal reflux disease in infants and children [38].…”
Section: Ppi For H Pylori Eradicationmentioning
confidence: 99%